Social isolation shortens telomeres in African Grey parrots (Psittacus erithacus erithacus). - Denise Aydinonat; Dustin J Penn; Steve Smith; Yoshan Moodley; Franz Hoelzl; Felix Knauer; Franz Schwarzenberger (PLoS ONE, 2014)
Telomeres, the caps of eukaryotic chromosomes, control chromosome stability and cellular senescence, but aging and exposure to chronic stress are suspected to cause attrition of telomere length. We investigated the effect of social isolation on telomere length in the highly social and intelligent African Grey parrot (Psittacus erithacus erithacus). Our study population consisted of single-housed (n = 26) and pair-housed (n = 19) captive individuals between 0.75 to 45 years of age. Relative telomere length of erythrocyte DNA was measured by quantitative real-time PCR. We found that telomere length declined with age (p<0.001), and socially isolated parrots had significantly shorter telomeres compared to pair-housed birds (p<0.001) - even among birds of similar ages. Our findings provide the first evidence that social isolation affects telomere length, which supports the hypothesis that telomeres provide a biomarker indicating exposure to chronic stress.